2011
DOI: 10.1016/j.jmb.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

S-Glutathionylation of Cysteine 99 in the APE1 Protein Impairs Abasic Endonuclease Activity

Abstract: Human apurinic/apyrimidinic (AP) endonuclease 1 (APE1) is a central participant in the base excision repair pathway, exhibiting AP endonuclease activity that incises the DNA backbone 5′ to an abasic site. Besides its prominent role as a DNA repair enzyme, APE1 was separately identified as a protein called redox effector factor 1, which is able to enhance the DNA binding activity of several transcription factors through a thiol-exchange-based reduction–oxidation mechanism. In the present study, we found that hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Site-directed mutagenesis of Cys residues within the redox regulatory portion of the protein (Cys65Ala, Cys93Ala and Cys99Ala) revealed that mutants containing Cys99Ala were not affected by oxidation, indicating that the oxidative inactivation of APE1 activity requires Cys99. The redox active Cys99 site was further confirmed by MS analysis, which identified glutathionylation with GSH/diamide treatment and –SOH, -SO 2 H and disulfides with H 2 O 2 treatment [214,215]. …”
Section: Redox Regulation Of Epigeneticsmentioning
confidence: 99%
“…Site-directed mutagenesis of Cys residues within the redox regulatory portion of the protein (Cys65Ala, Cys93Ala and Cys99Ala) revealed that mutants containing Cys99Ala were not affected by oxidation, indicating that the oxidative inactivation of APE1 activity requires Cys99. The redox active Cys99 site was further confirmed by MS analysis, which identified glutathionylation with GSH/diamide treatment and –SOH, -SO 2 H and disulfides with H 2 O 2 treatment [214,215]. …”
Section: Redox Regulation Of Epigeneticsmentioning
confidence: 99%
“…As will be discussed below, specific portions of the protein are still being assigned to particular function(s), but currently, the redox activity has been associated with the N-terminus of the protein, whereas the majority of the protein, the C-terminus, is essential for its DNA repair activities. Post-translational modifications of APE1, consisting of phosphorylation, acetylation, glutathionylation and ubiquitination, can regulate protein function, although the biological significance of these modifications is not yet fully understood [34,35,36]. …”
Section: Ber Proteins In Clinical Treatmentsmentioning
confidence: 99%
“…Documented PTMs detected in APEX1 include phosphorylation 96,97 , acetylation 98100 , ubiquitination 101 , and S-nitrosylation (Table 1) 96,102 . However, S-glutathionylation also occurs in response to the altered redox state of the cell 103 . Glutathionylation, addition of a glutathione group, occurs at cysteine residues and three candidate cysteines are located in the redox responsive domain of APEX1 103 .…”
Section: Post-translational Modifications Affecting Function and Pmentioning
confidence: 99%
“…However, S-glutathionylation also occurs in response to the altered redox state of the cell 103 . Glutathionylation, addition of a glutathione group, occurs at cysteine residues and three candidate cysteines are located in the redox responsive domain of APEX1 103 . As cysteine modifications include disulfide bridges, S-nitrosylation, and S-glutathionylation, understanding the competition between different PTMs and how they impact APEX1 function is crucial.…”
Section: Post-translational Modifications Affecting Function and Pmentioning
confidence: 99%
See 1 more Smart Citation